Lithium-containing oxide, electrode and battery
A cation disordered lithium-containing oxide with a rock salt structure and specific elemental composition addresses voltage hysteresis and low efficiency issues, enhancing energy conversion and density in lithium-ion batteries.
Patent Information
- Application Number
- CN202380041939.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-04
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-03
AI Technical Summary
Cation disordered lithium-containing oxides exhibit voltage hysteresis, large irreversible capacity, and low energy conversion efficiency during charge and discharge processes.
A lithium-containing oxide with a cation disordered rock salt structure, characterized by specific Li-NMR spectral signals and compositional ranges, is developed, which includes elements like Cr, Mn, Fe, Co, Ni, Cu, Si, P, S, V, and Ge, with a crystalline and amorphous phase, enhancing lithium ion diffusion.
The lithium-containing oxide achieves high energy conversion efficiency with reduced voltage hysteresis and irreversible capacity, improving the energy density of lithium-ion batteries.
Smart Images

Figure CN119255969A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to lithium-containing oxides, electrodes, and batteries. Background Art
[0002] It is known that there are secondary batteries that are charged and discharged by the movement of alkali metal ions between the positive electrode and the negative electrode. Among such secondary batteries, lithium ion secondary batteries are representative and have been put into practical use as small power sources for mobile phones and laptop computers, and can be used as large power sources such as power sources for automobiles such as electric vehicles and hybrid vehicles or power sources for distributed power storage, so their demand is increasing.
[0003] As a positive electrode material for lithium ion secondary batteries, Li-ion ions having a cation disordered rock salt type crystal structure are known. 1.2 Mn 0.4 Ti 0.4 O 2 , Li 1.3 Mn 0.4 Nb 0.3 O 2 Lithium-containing oxides such as LiCoO 2 Compared with lithium-containing layered oxides, it is possible to increase the lithium content in the composition and become a positive electrode material with high energy density. 2+ Low valence transition metals and V 4+ The cation disordered lithium oxide and fluoride oxide composed of high-valent transition metals, and further introduced Li 2 SO 4 Cation disordered lithium oxides containing lithium salts such as lithium salts (Non-Patent Document 1, Patent Documents 1 to 3).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-92958
[0007] Patent Document 2: Japanese Patent Application Publication No. 2020-534234
[0008] Patent Document 3: International Publication No. 2017 / 169599
[0009] Non-patent literature
[0010] Non-patent literature 1: Nature Communications 7, Article number: 13814 (2016) Summary of the invention
[0011] Problems to be solved by the invention
[0012] Among them, the previous cation disordered lithium-containing oxides have a voltage hysteresis between charge and discharge, a large irreversible capacity, and a low energy conversion efficiency between charge and discharge.
[0013] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a cation disordered lithium-containing oxide having high energy conversion efficiency, and an electrode and a battery using the same.
[0014] Means for solving problems
[0015] The present disclosure includes the following embodiments [1] to
[11] .
[0016] [1] A lithium-containing oxide having a cation disordered rock salt structure, which is used in the determination of solid 7 In the Li-NMR spectrum, within the chemical shift range of -3000 to 3000 ppm with the peak of a 1 mol / L LiCl aqueous solution set to 0 ppm, a signal 1 having a half-value width greater than 0 ppm and less than 40 ppm and a signal 2 having a half-value width greater than 100 ppm and less than 2000 ppm were observed.
[0017] The integrated intensity of the signal 1 is greater than 0% and less than or equal to 60% of the total integrated intensity of the signal 1 and the signal 2.
[0018] [2] The lithium-containing oxide according to [1], which has the general formula: Li x M' a M” b Z c O 2-e X d Represents, wherein 1<x≤1.40, 0.55≤a≤0.90, 0.05≤b≤0.22, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is Si, or two or more elements consisting of Si and at least one element selected from the group consisting of P, S, V and Ge, Z is an element other than Li, O, M', M" and halogen, and X is a halogen element.
[0019] [3] The lithium-containing oxide according to [1], which has the general formula: Li x M' a M” b Z c O 2-e X dRepresents, wherein 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is V, or two or more elements consisting of V and at least one element selected from the group consisting of P, S, Si and Ge, Z is an element other than Li, O, M', M" and halogen, and X is a halogen element.
[0020] [4] The lithium-containing oxide according to [1], which has the general formula: Li x M' a M” b Z c O 2-e X d Represents, wherein 1<x≤1.40, 0.55≤a≤0.90, 0.05≤b≤0.22, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is Ge, or two or more elements consisting of Ge and at least one element selected from the group consisting of P, S, Si and V, Z is an element other than Li, O, M', M" and halogen, and X is a halogen element.
[0021] [5] The lithium-containing oxide according to [1], which has the general formula: Li x M' a M” b Z c O 2-e X d Represents, wherein 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is at least two or more elements selected from the group consisting of Si, P, S, V and Ge, Z is an element other than Li, O, M', M" and halogen, and X is a halogen element.
[0022] [6] The lithium-containing oxide according to any one of [1] to [5], wherein the half-value width of the peak observed in the range of 2θ of 42 to 46° when powder X-ray diffraction is measured at 25°C using CuKα radiation is 0.5 to 5°.
[0023] [7] A lithium-containing oxide, comprising 8 to 12% by mass of Li, 35 to 56% by mass of at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, namely M', and more than 0% by mass and less than 15% by mass of at least one element selected from the group consisting of Si, P, S, V and Ge, namely M", wherein a diffraction pattern derived from a cation disordered rock salt structure is observed when powder X-ray diffraction is measured using CuKα radiation at 25°C, and when solid 7 In the Li-NMR spectrum, within the chemical shift range of -3000 to 3000 ppm with the peak of a 1 mol / L LiCl aqueous solution set to 0 ppm, a signal 1 having a half-value width greater than 0 ppm and less than 40 ppm and a signal 2 having a half-value width greater than 100 ppm and less than 2000 ppm are observed, and the integrated intensity of the signal 1 is greater than 0% and less than 60% relative to the sum of the integrated intensities of the signal 1 and the signal 2.
[0024] [8] The lithium-containing oxide according to any one of [1] to [7], which has an amorphous phase.
[0025] [9] An electrode comprising the lithium-containing oxide according to any one of [1] to [8].
[0026]
[10] A non-aqueous secondary battery comprising the electrode described in [9].
[0027]
[11] A lithium-containing oxide having a crystalline phase and an amorphous phase of a cation disordered rock salt type structure,
[0028] In the determination of solid 7 In the Li-NMR spectrum, within the chemical shift range of -3000 to 3000 ppm with the peak of a 1 mol / L LiCl aqueous solution set to 0 ppm, a signal 1 having a half-value width greater than 0 ppm and less than 40 ppm and a signal 2 having a half-value width greater than 100 ppm and less than 2000 ppm were observed.
[0029] The integrated intensity of the signal 1 is greater than 0% and less than or equal to 60% of the total integrated intensity of the signal 1 and the signal 2.
[0030] Effects of the Invention
[0031] According to the present disclosure, it is possible to provide a cation-disordered lithium-containing oxide having high energy conversion efficiency, and an electrode and a battery using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The solids containing lithium oxides of Examples 1 to 3 and Comparative Example 1 are shown. 7 Figure 2. Li-NMR spectrum.
[0033] Figure 2 This is a diagram showing an electron beam diffraction image of the sample of Example 2.
[0034] Figure 3 This is a diagram showing a dark field observation image of the sample of Example 2 using a transmission microscope. DETAILED DESCRIPTION
[0035] The lithium-containing oxide of one embodiment of the present disclosure has a cation disordered rock salt structure. 7 In the Li-NMR spectrum, in the range of chemical shift of -3000 to 3000 ppm with the peak of 1 mol / L LiCl aqueous solution set to 0 ppm, signal 1 with a half-value width greater than 0 ppm and less than 40 ppm and signal 2 with a half-value width greater than 100 ppm and less than 2000 ppm are observed, and the integrated intensity of signal 1 is greater than 0% and less than 60% relative to the total of the integrated intensities of signal 1 and signal 2. According to such a lithium-containing oxide, the voltage hysteresis and irreversible capacity between charge and discharge are small, and the energy conversion efficiency between charge and discharge is improved. In addition, in this specification, unless otherwise specified, the solid 7 The chemical shift in the Li-NMR spectrum refers to a chemical shift in which the peak of a 1 mol / L LiCl aqueous solution is set to 0 ppm.
[0036] In addition, in this specification, the integration ratio of signal 1 and the integration ratio of signal 2 refer to the total integrated intensity of signal 1 and signal 2 relative to the integrated intensity of signal 1 and signal 2 (%).
[0037] The half value width of signal 1 may be 35 ppm or less, 30 ppm or less, 25 ppm or less, or 20 ppm or less, or 0.01 ppm or more, or 0.1 ppm or more. In addition, the half value width of signal 1 may be 0.01 to 40 ppm, 0.01 to 35 ppm, or 0.1 to 30 ppm.
[0038] Signal 1 may be a signal observed at a chemical shift of -1000 to 1000 ppm, -500 to 500 ppm, -100 to 100 ppm, -50 to 50 ppm, or -10 to 50 ppm.
[0039] Signal 1 may have a half-value width and chemical shift within the above range and may have one or more peaks. When two or more signals 1 are observed, they may be observed in two regions where the chemical shift is in the range of -20 to 10 ppm and greater than 10 ppm and less than 50 ppm. Among them, the signal observed in the range of chemical shift of -20 to 10 ppm is also referred to as signal 1-1, and the signal observed in the range of chemical shift greater than 10 ppm and less than 60 ppm is also referred to as signal 1-2.
[0040] Signal 1-1 may be a signal observed at a chemical shift of -15 to 8 ppm, -10 to 5 ppm, or -5 to 3 ppm. The half-value width of signal 1-1 may be 35 ppm or less, 30 ppm or less, 25 ppm or less, or 20 ppm or less, and may be 0.01 ppm or more, or 0.1 ppm or more. In addition, the half-value width of signal 1-1 may be 0.01 to 40 ppm, 0.01 to 35 ppm, or 0.1 to 30 ppm.
[0041] Signal 1-2 may be a signal observed in a chemical shift range of 15 to 50 ppm, 25 to 45 ppm, or 30 to 40 ppm. The half-value width of signal 1-2 may be below 35 ppm, below 30 ppm, below 25 ppm, or below 20 ppm, and may be above 0.01 ppm or above 0.1 ppm. In addition, the half-value width of signal 1-2 may be 0.01 to 40 ppm, 0.01 to 35 ppm, or 0.1 to 30 ppm.
[0042] The integral ratio of signal 1 can be less than 50%, less than 40%, less than 30%, less than 20% or less than 15%, can be more than 0.01%, more than 0.1%, can be 0.01% to 50%, 0.01% to 40%, 0.1% to 30% or 0.3 to 20%.
[0043] When both signal 1-1 and signal 1-2 are observed, the integral ratio of signal 1-1 may be less than 40%, less than 30%, less than 20%, or less than 15%, may be more than 0.01%, more than 0.1%, may be 0.01% to 40%, 0.01% to 30%, 0.1% to 20%, or 0.3 to 15%. It should be noted that when both signal 1-1 and signal 1-2 are observed, the integral ratio of signal 1-1 and signal 1-2 is the ratio (%) of the integral intensity of each of signal 1-1 and signal 1-2 to the total integral intensity of signal 1-1, signal 1-2, and signal 2.
[0044] When both signal 1-1 and signal 1-2 are observed, the integral ratio of signal 1-2 can be less than 30%, less than 20%, less than 15%, less than 10% or less than 5%, can be more than 0.01%, more than 0.1%, can be 0.01% to 30%, 0.01% to 20%, 0.1% to 15% or 0.3 to 10%.
[0045] The half-value width of signal 2 may be 150 to 1800 ppm, 200 to 1500 ppm, or 250 to 1300 ppm.
[0046] Signal 2 may be a signal observed at a chemical shift of -1000 to 1000 ppm, -500 to 900 ppm, -300 to 800 ppm, -200 to 700 ppm, or -150 to 600 ppm.
[0047] Signal 2 may have a half-value width and a chemical shift within the above ranges, and may have one or more peaks.
[0048] The lithium-containing oxide of the present embodiment may be a compound represented by the following formula (1).
[0049] Li x M' a M” b Z c O 2-e X d (1)
[0050] In formula (1), 1<x≤1.40, which may be 1.03≤x≤1.36.
[0051] In formula (1), 0.40≤a≤0.90, may be 0.45≤a≤0.87, or may be 0.50≤a≤0.85.
[0052] In formula (1), 0.01≤b≤0.35, may be 0.05≤b≤0.30, or may be 0.07≤b≤0.25.
[0053] In addition, 2≤x+a+b≤2.2.
[0054] In formula (1), 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70.
[0055] In formula (1), M' contains at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu. M" is at least one element selected from the group consisting of Si, P, S, V and Ge.
[0056] In the formula (1), Z is an element other than Li, O, M', M", and halogen, and X is a halogen element.
[0057] The lithium-containing oxide of the present embodiment may also have an amorphous phase while having a crystalline phase. The crystalline phase may be dispersed in the amorphous phase. The presence of the amorphous phase tends to improve the diffusion of lithium ions in the material. The alkali metal-containing oxide of the present embodiment may also have a crystalline phase (crystallite) having an average particle size of 1 to 30 nm in terms of equivalent circle diameter. The average particle size of the crystalline phase may be 1 to 20 nm in terms of equivalent circle diameter, and may be 1 to 15 nm. Here, the amorphous phase can be confirmed by observation using a transmission electron microscope (TEM).
[0058] In addition, the lithium-containing oxide of the present embodiment may also contain 8 to 12 mass % of Li, 35 to 56 mass % of at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, namely M', and greater than 0 mass % and less than 15 mass % of at least one element selected from the group consisting of Si, P, S, V and Ge, namely M". In addition to the above-mentioned Li, M' and M", the lithium-containing oxide may also contain elements other than Li, O, M', M" and halogens. As such elements, for example, alkali metal elements other than Li and elements and halogen elements of Groups 2 to 16 of the periodic table may be used. As alkali metals other than Li, Na, K, Rb, and Cs can be listed. As Groups 2 to 16 of the periodic table, Na, K, Rb, and Cs can be listed. The elements of group 6 may be metal elements, and Al and the like may be cited. The halogen element may include at least one element selected from the group consisting of F, Cl, Br and I, may include at least one of F and Cl, and may include F. The content of the halogen element may be 5% by mass or less relative to the total amount of the lithium-containing oxide. The lithium-containing oxide of the present embodiment may also not be a single phase. That is, it may also include lithium-containing oxides other than lithium-containing oxides having a cationic disordered rock salt structure. Therefore, when powder X-ray diffraction measurement is performed using CuKα rays at 25°C, diffraction patterns other than the diffraction pattern derived from the cationic disordered rock salt structure can be observed together. The lithium-containing oxide may also have an amorphous phase while having a crystalline phase (microcrystals).
[0059] The content of Li in the lithium-containing oxide of the present embodiment may be 8.05 to 11.6% by mass, or 8.1 to 11.4% by mass. The content of M' in the lithium-containing oxide of the present embodiment may be 35.5 to 54% by mass, or 36 to 53% by mass. The content of M" in the lithium-containing oxide of the present embodiment may be 1 to 15% by mass, or 2 to 14.5% by mass. The lithium-containing oxide of the present embodiment may also contain 1 to 10% by mass of at least one of Si and P, or 1.5 to 8.5% by mass, or 2 to 7% by mass.
[0060] M" may contain Si. That is, M" may be Si, or two or more elements selected from Si and at least one element selected from the group consisting of P, S, V and Ge. In this case, in formula (1), 1<x≤1.40, 0.55≤a≤0.90, 0.05≤b≤0.22, 1.8≤x+a+b≤2.2 may be satisfied.
[0061] M" may contain V. That is, M" may be V, or two or more elements consisting of V and at least one element selected from the group consisting of Si, P, S and Ge. In this case, in formula (1), 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2 may be satisfied. V may be pentavalent.
[0062] M" may contain Ge. That is, M" may be Ge, or two or more elements selected from the group consisting of Ge and at least one element selected from Si, P, S and V. In this case, in formula (1), 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2 may be satisfied. Ge may be tetravalent.
[0063] M" may contain at least two or more selected from the group consisting of Si, P, S, V and Ge, and may contain at least one of Si and P. In this case, in formula (1), wherein, 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2.
[0064] In formula (1), Z may be, for example, an alkali metal element other than Li and an element of Group 2 to Group 16 of the periodic table. Examples of Z include Na, K, Rb, Cs, Al, Mg, Ca, Zr, Nb, Mo, Ru, W, Sn, etc. Z may be a metal element.
[0065] In the formula (1), c may be 0.10 or less, 0.05 or less, 0.01 or less, or substantially 0.
[0066] In formula (1), X may include at least one element selected from the group consisting of F, Cl, Br, and I, may include at least one of F and Cl, and may include F.
[0067] In formula (1), d may be less than or equal to 0.60, less than or equal to 0.40, less than or equal to 0.20, less than or equal to 0.10, less than or equal to 0.05, less than or equal to 0.01, or substantially 0. d may be greater than or equal to 0.001. In addition, d may be between 0.001 and 0.6, between 0.001 and 0.4, or between 0.001 and 0.2. e may be less than or equal to 0.60, less than or equal to 0.40, less than or equal to 0.20, less than or equal to 0.10, less than or equal to 0.05, less than or equal to 0.01, or substantially 0. e may be greater than or equal to 0.001. In addition, e may be between 0.001 and 0.6, between 0.001 and 0.4, or between 0.001 and 0.2.
[0068] The lithium-containing oxide of the present embodiment may be: when a powder X-ray diffraction measurement is performed using CuKα rays, a diffraction pattern belonging to a cation disordered rock salt structure having a characteristic of a crystal space group Fm-3m is observed, and the half-value width of the peak observed in the range of 2θ of 42 to 46° is 0.5 to 5°. In the cation disordered rock salt structure having a characteristic of a crystal space group Fm-3m, the peak observed in the range of 2θ of 42 to 46° originates from the reflection of the (200) plane.
[0069] The method for producing the lithium-containing compound is not particularly limited, but a method of mechanochemically mixing an oxide containing Li and M' and having a rock salt composition (rock salt composition oxide) with a lithium salt containing M" using a ball mill can be cited. Examples of the rock salt composition oxide include LiCrO 2 、LiMnO 2 、LiFeO 2 、LiCoO 2 、LiNiO 2 、LiCuO 2 As lithium salt, LiVO 4 , Li 4 SiO 4 , Li 2 SiO 3 , Li 3 P 0.5 V 0.5 O 4、 Li 3.5 Si 0.5 P 0.5 O 4、 Li 4 GeO 4 , Li 3 PO 4 The conditions of the ball mill are not particularly limited, but the rotation speed may be 100 to 700 rpm, and the mixing time may be 0.5 to 72 hours.
[0070] The lithium-containing oxide of this embodiment can be used in materials for batteries (lithium-ion batteries, etc.). That is, the battery of this embodiment includes the above-mentioned lithium-containing oxide. The battery can be a primary battery or a secondary battery. In addition, the battery can be a non-aqueous secondary battery. In the battery, the above-mentioned lithium-containing oxide can be included in the electrode.
[0071] The battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte disposed between the positive electrode and the negative electrode.
[0072] The positive electrode of this embodiment includes a positive electrode active material. The positive electrode active material of this embodiment includes a lithium-containing oxide of this embodiment. The positive electrode includes a current collector and a positive electrode mixture supported on the current collector. The positive electrode mixture can also form a positive electrode mixture layer on the current collector.
[0073] The positive electrode mixture contains a positive electrode active material and may contain a conductive material, a binder, etc. as necessary.
[0074] As the conductive material, carbon materials such as natural graphite, artificial graphite, coke, and carbon black can be listed. As the binder, thermoplastic resins can be listed, specifically, fluororesins such as polyvinylidene fluoride (hereinafter, also referred to as "PVDF"), polytetrafluoroethylene, tetrafluoroethylene, hexafluoropropylene, vinylidene fluoride copolymers, hexafluoropropylene, vinylidene fluoride copolymers, and tetrafluoroethylene perfluorovinyl ether copolymers can be listed; and polyolefin resins such as polyethylene and polypropylene can be listed. As the collector, Al, Ni, stainless steel, etc. can be used.
[0075] As a method for carrying a positive electrode mixture on a current collector, there can be listed a method of press molding, a method of pasting the electrode mixture using an organic solvent, etc., applying it to the current collector, and pressing it after drying to fix it, etc. In the case of pasting, for example, a slurry containing the above-mentioned positive electrode active material, a conductive material, a binder and an organic solvent is prepared. As an organic solvent, there can be listed amines such as N,N-dimethylaminopropylamine and diethyltriamine; ethers such as ethylene oxide and tetrahydrofuran; ketones such as methyl ethyl ketone; esters such as methyl acetate; aprotic polar solvents such as dimethylacetamide and N-methyl-2-pyrrolidone, etc. As a method for coating the electrode mixture on the current collector, for example, there can be listed a slit die extrusion coating method, a screen coating method, a curtain coating method, a doctor blade coating method, a gravure coating method, an electrostatic spray, etc.
[0076] The negative electrode of the battery is not particularly limited, and may be a negative electrode containing a negative electrode active material and, if necessary, a conductive aid, a binder, etc. For example, the negative electrode active material of a lithium ion battery may include simple substances of elements such as Li, Si, P, Sn, Si-Mn, Si-Co, Si-Ni, In, Au, and alloys or composites containing these elements, carbon materials such as graphite, and materials in which lithium ions are embedded between the layers of the carbon material.
[0077] The electrolyte of the battery is not particularly limited, and an electrolyte obtained by dissolving an alkali metal salt in an organic solvent can be used. In addition, the electrolyte can also be a solid electrolyte. As the alkali metal salt, iodide salts, tetrafluoroborate, hexafluorophosphate, bis(fluorosulfonyl)imide salts, bis(trifluoromethylsulfonyl)imide salts, etc. can be listed.
[0078] The organic solvent contained in the electrolyte is not particularly limited, and non-aqueous solvents, for example, cyclic carbonate esters such as ethylene carbonate (EC) or propylene carbonate (PC), straight-chain carbonate esters such as dimethyl carbonate (DMC), diethyl carbonate (DEC), or ethyl methyl carbonate (EMC), or sultones, etc. can be listed. The solvent can also be used alone or in combination of two or more.
[0079] Example
[0080] (Example 1)
[0081] LiMnO 2 It is obtained by mixing lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and manganese (III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) at a molar ratio of 1:1 and calcining the mixture at 900°C for 12 hours in an argon atmosphere. 3 VO 4 It is obtained by mixing lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and vanadium (V) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) at a molar ratio of 3:1 and calcining the mixture at 650°C for 12 hours in the air. 2 Powder and Li 3 VO 4 The powders were mixed at a molar ratio of 0.9:0.1, and zirconia balls with a diameter of 4 mm and the mixed powder were introduced into a zirconia ball mill container in a mass ratio of 65:1. The ball mill container was introduced into a planetary ball mill device (PM200 manufactured by Retsch Co.), and ball milling was performed at a rotation speed of 500 rpm for 48 hours to obtain a cation disordered lithium-containing oxide.
[0082] (Examples 2 to 11 and Comparative Examples 1 to 4)
[0083] The raw materials were obtained as follows.
[0084] Li 4 SiO 4 The obtained material was obtained by mixing lithium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and silicon dioxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) at a molar ratio of 2:1 and calcining the mixture at 900° C. for 4 hours in the atmosphere.
[0085] Li 2 SiO 3 Reagents produced by Kojundo Chemical Laboratory Co., Ltd. were used.
[0086] Li 4 GeO 4 It is obtained by mixing lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and germanium oxide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) at a molar ratio of 2:1 and calcining the mixture at 650°C for 12 hours in the atmosphere.
[0087] Li 3 P 0.5 V 0.5 O 4 It is obtained by mixing lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), diammonium hydrogen phosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and vanadium (V) oxide at a molar ratio of 6:2:1, and calcining the mixture at 800°C for 10 hours in the atmosphere.
[0088] Li 3.5 Si 0.5 P 0.5 O 4 It is obtained by the following method: lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and Li 3 PO 4 The resulting mixture was mixed with silicon dioxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) at a molar ratio of 2:1:1, and calcined at 900° C. for 10 hours in an argon atmosphere.
[0089] Li 3 PO 4 The method is as follows: lithium hydroxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and diammonium hydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) are dissolved in ion exchange water at a molar ratio of 3:1, and the resulting precipitate is filtered and dried at 80°C.
[0090] LiCrO 2The chromium carbonate was obtained by mixing lithium carbonate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and chromium (III) oxide (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) at a molar ratio of 1:1 and calcining the mixture at 800°C for 15 hours in an argon atmosphere.
[0091] Li 1.2 Mn 0.5 Ti 0.3 O 2 It is obtained by the following method: lithium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and manganese (III) oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and manganese (IV) oxide and TiO 2 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was weighed in a molar ratio of 6:2:1:3, mixed with ethanol and 8 mm diameter zirconium oxide balls using a wet ball mill, filtered, and the dried mixed powder was calcined at 900°C for 12 hours in an argon atmosphere.
[0092] The above raw materials were used, the formulation was changed as shown in Table 1, and ball milling was performed under the same conditions as in Example 1 except for Comparative Example 3 to produce a lithium-containing oxide.
[0093] <Charge and discharge test>
[0094] (1) Preparation of positive electrode
[0095] Each lithium-containing compound of the embodiments and comparative examples except comparative example 3, acetylene black (trade name: HS-100, manufactured by Denka Co., Ltd.) as a conductive material, and polytetrafluoroethylene (PTFE, product number: 6-J, Chemours-Mitsui Fluoroproducts Co., Ltd.) as a binder are weighed separately in a manner to form a composition of positive electrode active material: conductive material: binder = 70:20:10 (mass ratio). Then, the positive electrode active material and the conductive material are thoroughly mixed with an agate mortar, and the binder is added and further mixed. 7 mg of the mixture is weighed and drawn into a circle on the mortar. The drawn mixture is crimped to an aluminum mesh (100 mesh, manufactured by The Nilaco Co., Ltd.) with a thickness of 110 μm as a collector to obtain a positive electrode containing a positive electrode active material.
[0096] For Comparative Example 3, Li 1.2 Mn 0.5 Ti 0.3 O 2It is weighed with acetylene black (trade name: HS-100, manufactured by Denka Co., Ltd.) in a mass ratio of 9:1, and ball-milled with a zirconia ball of 8 mm in diameter at a rotation speed of 500 rpm for 9 hours. The mixed powder is added and kneaded with an N-methyl-2-pyrrolidone (NMP) solution of acetylene black and PVDF as a binder (KF Polymer, product number: L#1120, manufactured by Kureha Co., Ltd.) in a ratio of 72:18:10 (mass ratio) of positive electrode active material: acetylene black: PVDF to adjust the paste-like positive electrode composite. When preparing the positive electrode composite, the viscosity of the paste is adjusted by adding NMP. The obtained positive electrode composite is coated on an Al foil with a thickness of 40 μm, which serves as a collector, and after being air-dried at 60°C for 1 hour, it is vacuum-dried at 150°C for 8 hours to obtain a positive electrode.
[0097] (2) Fabrication and evaluation of Li half-cells
[0098] The above-mentioned positive electrode, a polyethylene porous film (thickness 16 μm) as a separator, and 1 M LiPF 6 A coin-type battery CR2032 type was assembled using a solution (the solvent is a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:35:35) and metallic lithium as a counter electrode. It should be noted that the assembly of the battery was carried out in a glove box with an argon atmosphere. Using the produced coin-type battery, a charge and discharge test was carried out under the following conditions at 25°C and a voltage range of 1.5 to 4.8V. Based on the results of the charge and discharge test, a graph was prepared with the battery capacity (mAh / g) as the horizontal axis and the battery voltage (V vsLi / Li + ) is taken as the charge-discharge curve on the vertical axis, and the area of the region enclosed by the curve and the horizontal axis is obtained for charging and discharging, respectively, to calculate the charge energy density and the discharge energy density. The results of the first discharge energy density and the energy conversion efficiency (ratio of discharge energy density to charge energy density (%)) are shown in Table 1.
[0099] Charge and discharge conditions: constant current constant voltage (CC-CV) charging at 30 mA / g and cut-off condition 6 mA / g.
[0100] Discharge conditions: constant current (CC) discharge at 30 mA / g.
[0101] Table 1
[0102]
[0103] <Solid 7 Li-NMR determination>
[0104] For each lithium-containing oxide obtained in the examples and comparative examples, solid 7 Li-NMR measurements were carried out at room temperature (25 °C) under the following conditions. The results are shown in Tables 2 and 3. Here, Signal 1 is a signal with a half-width greater than 0 ppm and 40 ppm or less for lithium with a relatively small influence from paramagnetic components in the sample, and Signal 2 refers to a signal with a half-width greater than 100 ppm and 2000 ppm or less for Li that is strongly influenced by paramagnetic components in the sample. In Tables 2 and 3, the signal integration ratio represents the ratio (%) of the integration intensity of each signal to the total integration intensity of Signal 1 and Signal 2. It should be noted that the integration intensity of each signal was calculated by curve fitting with a Gaussian function to separate the signals. The solid 7 Li-NMR spectra of the lithium-containing oxides of Examples 1 to 3 and Comparative Example 1 are shown in Figure 1 . It should be noted that Figure 1 in, the * signal is a spinning sideband that was not completely suppressed.
[0105] As a pretreatment, approximately 6 mg of the analysis sample was filled into a 1.3 mm φ zirconia rotor.
[0106] Solid 7 Li-NMR measurements were carried out as follows.
[0107] Spectrometer: AVANCE300 (manufactured by Bruker)
[0108] Observed nucleus: 7Li (resonance frequency 117 MHz)
[0109] Measurement method: MATPASS method
[0110] MAS condition: 50 kHz
[0111] Waiting time: 0.2 seconds
[0112] Number of accumulations: 81920 times
[0113] Measurement temperature: 25 °C
[0114] Reference substance: 1 mol / L LiCl aqueous solution
[0115] Table 2
[0116]
[0117] Table 3
[0118]
[0119] <X-ray diffraction>
[0120] Powder X-ray diffraction measurement was performed on each lithium-containing oxide of the embodiment and comparative example using a powder X-ray diffraction measuring device (Ultima IV manufactured by Rigaku Co., Ltd.). The measurement was performed by filling the lithium-containing oxide on a glass plate at room temperature, sealing the glass plate carrying the sample in an airtight sample stand with a beryllium window to avoid air and moisture, and measuring without exposure to the atmosphere. A CuKα ray source was used with an output power of 40 kV and 40 mA, and the diffraction angle range of 2θ = 10° to 90° was measured at a step of 0.02° and a speed of 2° / min. The results are shown in Table 4.
[0121] Table 4
[0122]
[0123] <Observation using a transmission electron microscope>
[0124] The measurement was carried out under the following conditions.
[0125] Equipment: Analytical electron microscope ARM200F, manufactured by JEOL Ltd.
[0126] Measurement conditions: Acceleration voltage 200 kV
[0127] Sample preparation: The lithium-containing oxide of Example 2 was prepared by a dry dispersion method in an inert atmosphere.
[0128] Figure 2 2 shows an electron beam diffraction image of the sample of Example 2. The circle indicated by BF in the figure is the observation position of the bright field image (not shown). Figure 2 The circles 1, 2, and 3 in FIG. 1 represent the insertion positions (openings) of the objective lens diaphragms. Figure 2 In the image, since multiple bright spots are observed to be arranged in a ring shape and halos are observed, it can be seen that a crystalline phase and an amorphous phase exist.
[0129] Figure 3 This is a diagram showing a dark field observation image of the sample of Example 2 using a transmission microscope. Figure 3 (A), (B) and (C) in Figure 2 The dark field observation image is obtained by inserting the objective lens aperture into positions 1, 2, and 3 in the image. Figure 3 The white granular structure in the middle represents a crystal phase. The crystal phase has a particle size of about 3 to 10 nm in terms of equivalent circle diameter.
Claims
1. A lithium-containing oxide having a cation disordered rock salt type structure, In the determination of solid 7 In the Li-NMR spectrum, within the chemical shift range of -3000 to 3000 ppm with the peak of a 1 mol / L LiCl aqueous solution set to 0 ppm, a signal 1 having a half-value width greater than 0 ppm and less than 40 ppm and a signal 2 having a half-value width greater than 100 ppm and less than 2000 ppm were observed. The integrated intensity of the signal 1 is greater than 0% and less than or equal to 60% of the total integrated intensity of the signal 1 and the signal 2.
2. The lithium-containing oxide according to claim 1, which has the general formula: Li x M' a M” b Z c O 2-e X d express, Wherein, 1<x≤1.40, 0.55≤a≤0.90, 0.05≤b≤0.22, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is Si, or two or more elements consisting of Si and at least one element selected from the group consisting of P, S, V and Ge, Z is an element other than Li, O, M', M", and halogen, X is a halogen element.
3. The lithium-containing oxide according to claim 1, which has the general formula: Li x M' a M” b Z c O 2-e X d express, Wherein, 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is V, or two or more elements consisting of V and at least one element selected from the group consisting of P, S, Si and Ge, Z is an element other than Li, O, M', M", and halogen, X is a halogen element.
4. The lithium-containing oxide according to claim 1, which has the general formula: Li x M' a M” b Z c O 2-e X d express, Wherein, 1<x≤1.40, 0.55≤a≤0.90, 0.05≤b≤0.22, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is Ge, or two or more elements consisting of Ge and at least one element selected from the group consisting of P, S, Si and V, Z is an element other than Li, O, M', M", and halogen, X is a halogen element.
5. The lithium-containing oxide according to claim 1, which has the general formula: Li x M' a M” b Z c O 2-e X d express, Wherein, 1<x≤1.30, 0.4≤a≤0.85, 0.05≤b≤0.30, 1.8≤x+a+b≤2.2, 0≤c≤0.20, 0≤d<0.70, 0≤e<0.70, M' is at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, M" is at least two or more selected from the group consisting of Si, P, S, V and Ge, Z is an element other than Li, O, M', M", and halogen, X is a halogen element. The lithium-containing oxide according to any one of claims 1 to 5, wherein the half-value width of a peak observed in the range of 2θ of 42 to 46° is 0.5 to 5° when powder X-ray diffraction is measured using CuKα radiation at 25°C.
7. A lithium-containing oxide comprising 8 to 12 mass % of Li, 35 to 56 mass % of at least one element selected from the group consisting of Cr, Mn, Fe, Co, Ni and Cu, namely M', and more than 0 mass % and less than 15 mass % of at least one element selected from the group consisting of Si, P, S, V and Ge, namely M' When powder X-ray diffraction was measured at 25°C using CuKα radiation, a diffraction pattern derived from a cationic disordered rock salt structure was observed. In the determination of solid 7 In the Li-NMR spectrum, within the chemical shift range of -3000 to 3000 ppm with the peak of a 1 mol / L LiCl aqueous solution set to 0 ppm, a signal 1 having a half-value width greater than 0 ppm and less than 40 ppm and a signal 2 having a half-value width greater than 100 ppm and less than 2000 ppm were observed. The integrated intensity of the signal 1 is greater than 0% and less than or equal to 60% of the total integrated intensity of the signal 1 and the signal 2. 8 . An electrode comprising the lithium-containing oxide according to claim 1 .
9. A battery comprising the electrode according to claim 8. 10 . The lithium-containing oxide according to claim 1 , which has an amorphous phase.
